Propuesta de un sistema de gestión ambiental para la finca bananera Venecia - Rodríguez Zambrano, Miguel Ángel (2014)
An Environmental Management System for Finance "Venice", was raised to 28.13 ha, and is located on the site of La Primavera, parish Change Region Machala, province of El Oro, Region Seven, which contribute to the proper implementation of the production process and its impact within the community, making it a center of reference production and good agricultural practices was raised, allowing the use of a methodology to audit the state in which the banana plantations are found, taking into account technical, legal, administrative, economic, environmental and community, each factor analyzed determine the state in which the Property is located, and this results is proposed System of Integrated Environmental Management contribute to the sustained development community and region in which the property is located; the variables that were considered in the study were: Technical Audit, Statutory audit, Management Audit and economic-financial audit which allowed the necessary information to the merits of the project, concluding that the proposed Environmental Management System has an efficient development approach keeping in mind the conservative view with the environment, and especially maximum productivity at minimum cost, compliance with laws and regulations by the state and society to be involved in business development.